دور الذكاء الاستراتيجي في تحقيق التفوق التنافسي من خلال القدرات الاستراتيجية في المؤسسات الاقتصادية - معلول, ليلة (Universty of Eloued جامعة الشهيد حمه لخضر, 2022)
الملخص: تهدف هذه الدراسة إلى التعرف على أثر الذكاء الاستراتيجي في تحقيق التنافسي من خلال القدرات الاستراتيجية، بوكالات السياحة والأسفار الفائزة بتنظيم عملية الحج (2013-2020)، بالاعتماد على أبعاد الذكاء الاستراتيجي (الاستشراف، الرؤية المستقبلية، تفكير النظم، الدافعية والشراكة) كمتغير مستقل والتفوق التنافسي كمتغير مستقل (التركيز على الزبون، المنافسة، ادارة معرفة الزبون)، القدرات الاستراتيجية كمتغير وسيط (المعرفة الفنية لتوليد القيمة، القدرة على توليد الموارد وامتلاكها، تقنيات الإدارة المستخدمة). ولقد اعتمدت الدراسة على المنهج الوصفي في الجانب النظري، والمنهج التحليلي الاستدلالي في الجانب التطبيقي منه، بالاعتماد على أسلوب المسح الاجتماعي، وتم استخدام أداة الاستبيان لمعرفة آراء عينة الدراسة المكونة من 259 متخذ قائد بهذه الوكالات، وتم تحليل النتائج بالاعتماد على برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS و SPSS Amos في نسختيهما 25، وتم اختبار نتائج الدراسة باستعمال أساليب إحصائية متعددة مثل: اختبار تحليل التباين الأحادي، اختبار t لعينتين مستقلتين، والاختبارات البعدية في حالة وجود فروق ذات دلالة إحصائية. وأظهرت الدراسة بأن توفر ابعاد الذكاء الإستراتيجي وأبعاده يساهم في تحقيق ابعاد القدرات الاستراتيجية، وأثبتت وجود فروق ذات دلالة إحصائية حول توفر ابعاد الذكاء الإستراتيجي تعزى لبعض البيانات الشخصية، تمتع الوكالات السياحية محل الدراسة بجميع ابعاد التفوق التنافسي. ومن خلال النتائج المتحصل عليها أوصت الطالبة بضرورة تفعيل بعد الشراكة، استخدام أبعاد الذكاء الإستراتيجي لترسيخ السمات القيادية، المحافظة على مكونات الذكاء الإستراتيجي المتوفرة في المؤسسات محل الدراسة وتفعيلها لتحقيق التفوق على المنافسين، الحرص على المشاركة في الدورات التكوينية لصالح متخذي القرارات لزيادة تفعيل أبعاد الذكاء الإستراتيجي ومسايرة كل جديد في المجال الذي ينشطون فيه، إنشاء نظام للذكاء الإستراتيجي داخل هذا النوع من المؤسسات يسهر على تطويرها. Résumé : فرنسية أو انجلزية This study aims to identify the impact of strategic intelligence in achieving competitiveness through strategic capabilities, in the winning tourism and travel agencies in organizing the Hajj process (2013-2020), relying on the dimensions of strategic intelligence (foresight, future vision, systems thinking, motivation and partnership) as an independent variable and superiority. Competitiveness as an independent variable (customer focus, competition, customer knowledge management), strategic capabilities as an intermediary variable (technical knowledge to generate value, ability to generate and own resources, management techniques used). The study relied on the descriptive approach in the theoretical aspect, and the analytical inferential approach in the applied aspect, depending on the social survey method, and the questionnaire tool was used to know the opinions of the study sample consisting of 259 leaders in these agencies, and the results were analyzed by relying on the Statistical Package for Social Sciences program. SPSS and SPSS Amos in their versions 25, and the results of the study were tested using multiple statistical methods such as: one-way analysis of variance test, t-test for two independent samples, and post-tests in the event of statistically significant differences. The study showed that the availability of dimensions of strategic intelligence and its dimensions contributes to achieving the dimensions of strategic capabilities, and proved the existence of statistically significant differences regarding the availability of dimensions of strategic intelligence due to some personal data. The tourism agencies under study enjoyed all dimensions of competitive superiority. Through the results obtained, the student recommended the necessity of activating the partnership dimension, using the dimensions of strategic intelligence to consolidate leadership traits, maintaining the components of strategic intelligence available in the institutions under study and activating them to achieve superiority over competitors, making sure to participate in formative courses for the benefit of decision makers to increase the activation of the dimensions of strategic intelligence. Keeping pace with everything new in the field in which they are active, establishing a system of strategic intelligence within this type of institution that ensures its development.
دراسة عينة من المؤسسات في الجزائر
أطروحة دكتوراه تخصص اقتصاد وتسيير مؤسسات في العلوم الاقتصادية
Keywords: الذكاء الاستراتيجي، ابعاد الذكاء الاستراتيجي، القدرات الاستراتيجية، التفوق التنافسي; :. strategic intelligence, dimensions of strategic intelligence, strategic capabilities, competitive advantage